A study on the viability of implementing halal food act in Malaysia / Fatimah Zahirah Mohd Damanhuri, Farah Lisa Ayub, and Yuhana Akmal Ghazali - Mohd Damanhuri, Fatimah Zahirah; Ayub, Farah Lisa; Akmal Ghazali, Yuhana (2009)
The demand of Halal food products has seen the global growth in Halal trade and Malaysia is no exception. Muslims and non-Muslims manufacturers are joining the wagon to produce Halal products for the masses. This raise concern whether the current law is adequate to protect Halal integrity and consumers against Halal abuses. Datas are collected through literatures and interviews conducted, besides critical analysis done on the current law. Currently there is no specific law to regulate the industry. This paper discusses the current development of Halal industry and makes reference to the low awareness level of the Muslim consumers. It also looks into the problems posed within the current Halal regulatory framework. All these are taken into consideration in arriving to the need and viability of a Halal Act. Halal Act is found to be necessary and important to patch up the hole of current inadequate law, to strengthen the consumer protection, and to realize Malaysia as Halal hub. The viability of Halal Act is met with a mixed answer. The implementation of the Halal Act though found necessary is met with the hurdle of state power in Islamic matter and their hesitancy to give up on the power. Halal Act may be materialised with consent of States. If States' consent cannot be solicited, the farthest we can go is to amend Trade Description Act 1972 to provide more consumer protection and stricter punishment for Halal abuse.